Stories from Langley : a glimpse inside the CIA - Mickolus, Edward F. ([Lincoln] : Potomac Books, An imprint of the University of Nebraska Press, 2014)
Applicants to the Central Intelligence Agency often asked Edward Mickolus what they might expect in a career there. Mickolus, a former CIA intelligence officer whose duties also included recruiting and public affairs, never had a simple answer. If applicants were considering a life in the National Clandestine Service, the answer was easy. Numerous memoirs show the lives of operations officers collecting secret intelligence overseas, conducting counterintelligence investigations, and running covert action programs. But the CIA isn't only about case officers in far-flung areas of the world, recr.
Careers in intelligence analysis / Volko F. Ruhnke -- The best speech I ever gave, the best thing I ever wrote / Martin Petersen -- Working with words and enjoying the view / John Hollister Hedley -- Never boring, often meaningful, and almost fun / Henry Appelbaum -- Briefing presidential candidates / John Helgerson -- The Soviets go on the LAMM / Michael D. Flint and Boyd Sutton -- Making the world safe through SAFE / Michael D. Flint -- Getting the facts right / Tony Williams -- An economist's look at the Soviet Union, and beyond / Robert E. Leggett -- Two of the "coolest" things I did working for the CIA / Robert Blackwell -- A cold war CIA analyst remembers / Anne Campbell Gruner -- Reminiscences of a checkered past / Nicholas Starr -- Reflections on an eclectic CIA career / Alan More -- A geographer looks back at 50 years with the CIA / Will Rogers -- An "out-of-body experience" : seeing the DI with new eyes / Jon Nowick -- Peasant at the creation : the agency's first terrorism analyst and beyond / Edward Mickolus -- Satellite imagery and the Afghan Task Force / Tom Sheridan -- Slideshow / Jeri DiGiulio -- Meanwhile, in Asia... / Merrily Baird -- On planet Congress / Martin Petersen -- In support, you never know where you might end up and what you might learn along the way / Dan King -- What is a promise worth? / Dan King -- An adventure in the Far East / Robert A. Morgan Jr -- First tour adventures : the mysterious case of the missing missionary / Hugh S. Pettis -- Out of the barn, into the beltway / Hazel Harrison -- Ed and a secretary : how I ended up at the CIa / Martin Petersen -- Traveling with the president / Frank Ryan -- Kh601 / Richard Irwin -- Our man in Havana's jails : temporary duty assignment in Hell / Walter E. Szuminski -- Operation Oshima / John Behling -- The other side of the CIA : my life as a CIA analyst / Gregor S.
JSTOR
Keywords: United States. -- Central Intelligence Agency -- Officials and employees -- Biography -- Anecdotes; United States. -- Central Intelligence Agency -- History -- Anecdotes; United States. -- Central Intelligence Agency; Intelligence officers -- United States -- Biography -- Anecdotes; Spies -- United States -- Biography -- Anecdotes; Intelligence service -- United States -- Anecdotes; Officiers de renseignements -- États-Unis -- Biographies -- Anecdotes; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; POLITICAL SCIENCE -- Intelligence & Espionage; Employees; Intelligence officers; Intelligence service; Spies; United States; Biographies; Anecdotes; History